PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI PT BANK BJB KANTOR CABANG KARAWANG - Salsabila Sukandar; Ujang Suherman; Thomas Nadeak (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study seeks to examine the influence of training and career development on employee performance, both individually and simultaneously. A quantitative approach with an associative design was applied, involving all 100 employees of PT Bank BJB Karawang Branch Office as respondents through a saturated sampling technique. Data were gathered using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 26. Prior to hypothesis testing, the instrument was evaluated through validity, reliability, and classical assumption tests to ensure the appropriateness of the regression model. The findings reveal that, partially, training has a positive effect in the moderate category on employee performance. In contrast, career development demonstrates a positive and statistically significant effect on performance. When tested simultaneously, training and career development significantly influence employee performance, contributing 76.5% to its variance. These results suggest that career development plays a more dominant role in enhancing employee performance, while training functions as a complementary supporting factor.